Two Models of Judicial Decision-Making - Weiler, Paul (Canadian Bar Review, 1968)
There are two different models of judicial decision-making that have been illustrated in American legal thinking. In this article the author thoroughly examines those models and illustrates the workings of each. First, the author discusses the adjudication of disputes model and examines its purpose, as well as its key elements and characteristics. He also examines its limits, namely the obstacle of polycentricity. The author then discusses the characteristics of the judicial-policy-maker model, as well as the various problems with which it is associated. In conclusion, the author suggests that although the judicial process in Canada fits neither model exactly, it is more or less organized along adjudicative lines.